Digital Marketing at TAP Air Portugal (Revista Lusófona de Economia e Gestão das Organizações, 2021)
This work aims to analyze the digital marketing developed by the company TAP Air Portugal and make a comparison with Easyjet and Emirates.As a methodology, in a first phase, a literature review was carried out in several databases: ProQuest, RCAAP, RECIL and Google Scholar.In a second stage, the detailed study of TAP Air Portugal was developed, in which the digital media used and the analysis of their performance were researched, through the digital communication tools: Google Trends, KWFinder, Page Speed Insights, GT Metrix, Similar Web and Site Analyzer.Finally, a comparison was made between TAP Air Portugal, Emirantes and EasyJet.As a fieldwork, an anonymous questionnaire was carried out to 735 customers - between 10/28/2019 and 10/30/2019 - who were at the Lisbon Airport and were preparing to board. This questionnaire allowed to verify the reach of TAP Air Portugal’s digital marketing.From this study it was found that they should continue to be focus on digital marketing, social networks, and mobile web, because they have a great impact on the promotion and sale of airline tickets